STRUCTURE COMMUNITY OF MANGROVE IN TANJUNG SUM VILLAGE DISTRICT OF KUALA KAMPAR, PELALAWAN REGENCY - Wahyudi Ramdano; Sofyan H. Siregar; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A study of mangrove forest at Tanjung Sum Village, Kuala Kampar District was conducted in January 2016. The aim of this study was to determine the spescies composition, dominant species and conditions of mangrove vegetation. The survey method was used in this research, where the observations were made with the line transect method. The results showed the mangrove ecosystem had 11 species of mangrove, consisting of 8 families. These species were Avicennia. alba, A. marina, Nypa fructicans, Bruguiera gymnorrhiza, Rizophora apiculata, R. stylosa, Lumnutzera littorea, Xylocarpus granatum, Sonneratia alba, Thespenia populnea and Acrostichum sp. The importance value was highest on the group tree of A. alba (i.e.137.69%, at Station 1), the highest importance values was at station 2 (207.69%) and station 3 (113.06%). In the group of seedling the highest INP was recorded on T. populnea (137.59%) at station 1, at station 2 on T. populnea with INP 165%, and the highest INP at station 3, R. stylosa was 193.04%.The conditions of mangrove ecosystem at all stations can be categorized in a good condition with very good criteria.